Assessment of habitat quality using macroinvertebrates and water quality parameters of a clay quarry wetland - Serpil Odabaşı (Journal of Advanced Research in Natural and Applied Sciences)
In this study, it is aimed to determine the habitat quality of the Bozalan quarry wetland by using diversity and a compositional index of benthic macroinvertebrates and some of the water quality parameters. The field studies were conducted in the three sampling sites chosen in the wetland three times (March, April, and May) in 2018. The standard multi-habitat method was used for the benthos sampling. Besides, water sampling was performed for the parameters measured in-situ and analyzed in the laboratory to reveal the water quality status of the wetland. Some of the diversity index values of the benthic macroinvertebrates including Shannon Wiener (H′), Evenness Index (EI), and BMWP-e were calculated. The results showed that the sampling sites were categorized into higher classes (I and II) in general according to water quality criteria of the surface waters of Turkey. Fourteen taxa of benthic macroinvertebrates were identified. The most dominant taxa were Coenagrion sp. (42.31%), Baetis rhodani (15.38%), and Physella acuta (10%) in the study area. The highest number of individuals of macroinvertebrates was obtained in March (62 ind./m2), meanwhile the highest taxa number was determined in May (10 taxa). The H′ index was reached its highest value in May (1.723), whereas the lowest value of the index was in March (1.054). The highest score of the BMWP-e was found in May (26), while the lowest score was found in April (16).